The culture of knowledge creation and knowledge sharing in successful Institute of Higher Learning (IHL): a literature review - Ahmad Lotfi, Nurul A‟tiyah; Ab Aziz, Nur Faizah; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
The culture of knowledge creation and knowledge sharing play very important role in the successful implementation of Knowledge Management in any Public or Private Institution of Higher Learning. A literature review study is being conducted to explore the culture of Knowledge Creation (KC) and Knowledge Sharing (KS) among the Community of Practice (CoP) in Malaysian Public Institution of Higher Learning (IHL) and the possible framework that has been practice in the education field.